2019
DOI: 10.1088/2051-672x/ab0afb
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigations on the tribological performance of hexagonal boron nitride nanofluids as lubricant for steel/steel friction pairs

Abstract: With laminated structure like graphite, hexagonal boron nitride nanoparticle (nano-hBN) performed excellent anti-wear and friction-reducing properties. In this paper, hBN nanofluids were prepared using sodium polyacrylate (PAAS) as dispersant in water. Four-ball tribometer and pin-on-disk tribometer were employed to evaluate the tribological performance and lubrication behavior of the above-prepared lubricating fluids during steel/steel friction. The worn surface of balls and disks was analyzed by scanning ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…The results showed the reduction in the COF and wear scar diameter by 35.7% and 35.2% respectively because of the formation of tribolayer on the counterpart surfaces. He et al 39 examined the tribological performance of hBN nanofluids by utilizing four‐ball and pin‐on‐disc tribotesting machines. The reduction in friction coefficient and wear scar diameter was observed by as much 29% and 15%, respectively, using hBN based nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed the reduction in the COF and wear scar diameter by 35.7% and 35.2% respectively because of the formation of tribolayer on the counterpart surfaces. He et al 39 examined the tribological performance of hBN nanofluids by utilizing four‐ball and pin‐on‐disc tribotesting machines. The reduction in friction coefficient and wear scar diameter was observed by as much 29% and 15%, respectively, using hBN based nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…22 hBN is a cheap lubricant that has better biodegradability and exhibits superior tribological properties upon mixing with conventional engine oils 15,16 or vegetable oils 1719 or water. 20…”
Section: Introductionmentioning
confidence: 99%
“…Among nanoparticle-based lubricants, hexagonal boron nitride (hBN) is a substance being studied with increasing interest. [15][16][17][18][19][20] hBN exhibits a laminated structure with an ultra-flat surface like graphite. Strong covalent boron-nitrogen bonds form the layer; weak Van der Waals force exists between layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the nanofluid with SDS had 4-5 days stability while without SDS the NPs agglomerated within 1 h after preparation. [116], polydopamine (PDA) [118], sodium dodecyl sulfate (SDS) [124,125], polyvinylpyrrolidone (PVP) [119], Igepal CO-520 [117], cetrimonium bromide (CTAB), and sodium dodecylbenzene sulfonate (SDBS) [119,184] Others dialkyl polyoxyethylene glycol thiophosphate ester (DTP-10, DTP-20) [154], oleylamine [93] benzalkonium chloride [90], sodium polyacrylate (PAAS) [159], SHMP (sodium hexametaphosphate), 1,4-butylene glycol [203], coconut diethanol amide (CDEA) [204]…”
Section: Surfactant Additionmentioning
confidence: 99%